Evaluating the Miyawaki Afforestation Technique in Urban Landscapes: Opportunities and Challenges - Osman Zeybek (Iconarp International Journal of Architecture and Planning)
Urban landscapes are increasingly dominated by impermeable surfaces, leading to significant ecological degradation, biodiversity loss, and urban heat island effects. The Miyawaki Afforestation Technique has gained attention as a potential solution for restoring urban green spaces by rapidly creating dense, biodiverse forests. This paper evaluates the potential and limitations of the Miyawaki method in the context of urban planning, with a focus on its ecological, social, and economic implications. While the method offers rapid forest establishment, increased biodiversity, and improved air quality, its applicability in varying climatic and urban conditions remains controversial. Issues such as land availability, maintenance intensity, and public perception of untamed green spaces present challenges for widespread adoption.